Bendroji lietuvių kalbos vedybų giminystės leksikos charakteristika - Buivydienė, Rūta (Baltistica, 1994)
GENERAL CHARACTERISTIC OF AFFINITIVE RELATIONSHIP TERMS IN THE LITHUANIAN LANGUAGE The vocabulary of affinity of the Lithuanian language consists of nearly 190 words, comprising 50 designates. More than half of the whole number of the affinitive kinship terms designate spouses and various hyponimic concepts. This subgroup of the system of affinitive terms (AT) is characterized by wide range of synonymy and a great stylistic variety. The core of the old Lithuanian AT system consisted of the terms of the 2nd degree of kinship (šešuras, anyta, dieveris, moša, uošvis, uošve, laigonas, svainė (AC type), marti, žentas (CA type) and the words, representing АСА type of the 3rd degree, that designate the marriage partner of a sibling of the same sex of the marriage partner (jentė "wife of the husband’s brother”; svainis „husband of the wife’s sister”). Other types of the 3rd degree affinity terms – CCA, CAC, ACC – as well as the concepts of the АСА type designating the marriage partner of the different sex sibling of the marriage partner were not everywhere and not regularly linguistically differentiated; the present names of these concepts are of later origin. The semantic development of some AT is to be explained by the replacement of the speaker (the ego) while leaving the same term for the same referent. It should be noted that there is sufficient grounds to speak of the rather strong correlation between the linguistic structure of the AT system in the Lithuanian language an the social organization of the very kinship relations. The linguistic criteria of differentiating kinship concepts have been changing in the course of time. Polysemy with respect to generation has been given up; while within the generation of the ego polysemy has widely expanded. The system of AT of the Lithuanian language is permeated by the process (that became notable already in the epoch of the old literature and has not yet entirely stopped even nowadays) of extinction of the opposition of affinitive terms according to the semantic indication of the ego sex. Two closely interrelated processes are characteristic of the whole development of the Lithuanian AT system: 1) the tendency of the loss of special, linguistic expression of the concepts of kinship, that has increased the polysemy of some kinship terms and the opposite process 2) the tendency of linguistic differentiation of the concepts of kinship, arising in attempt to avoid ambiguity.